Resepsi Politik Perempuan terhadap Program Perempuan Bicara di tvOne - Alifianisa, Safa; Roem, Elva Ronaning; Elian, Novi (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The study analyzes the meaning that female audiences derive from the Perempuan Bicara program on tvOne, specifically the episode titled